THE DEBATE REGARDING THE RIGHT TO FREEDOM OF EXPRESSION IN BRAZIL (CIPEEX, 2024)
THIS STUDY EXPLORES THE DEBATE ON THE RIGHT TO FREEDOM OF EXPRESSION IN BRAZIL, AIMING TO IDENTIFY THE REASONS AND ELEMENTS BEHIND THE CURRENT DISCUSSION REGARDING THIS FUNDAMENTAL RIGHT. IT EMPLOYS AN EXPLORATORY AND DESCRIPTIVE APPROACH, RELYING ON BIBLIOGRAPHIC RESEARCH OF MATERIALS RELATED TO THE RESEARCH OBJECTIVE, SUCH AS LAWS, SCIENTIFIC ARTICLES, DOCTRINES, JUDICIAL PRECEDENTS, AND ACADEMIC CONTENT. THE RESEARCH METHODOLOGY IS HYPOTHETICO-DEDUCTIVE. THE RIGHT TO FREEDOM OF EXPRESSION IS ANALYZED FROM THREE PERSPECTIVES: THE NATURAL PERSPECTIVE, ADDRESSING ITS ORIGINS, NATURAL LIMITATIONS, AND HISTORICAL CONTEXT WITHIN SOCIETY; THE LEGAL PERSPECTIVE, ENCOMPASSING STATUTORY LIMITATIONS, HIGH COURT JUDGMENTS, AND THE TREATMENT BY THE NATIONAL SUPREME COURT CONCERNING THIS RIGHT. NO PLACE IN THE WORLD UPHOLDS ABSOLUTE FREEDOM OF EXPRESSION, AS IT IS OFTEN SUBJECT TO OTHER FUNDAMENTAL RIGHTS. THEREFORE, THE DEBATE SURROUNDING FREEDOM OF EXPRESSION IN BRAZIL APPEARS TO BE A POLITICAL ONE.
Keywords: Brazil; Politics; Supreme; Freedom.